2013
DOI: 10.1159/000354139
|View full text |Cite
|
Sign up to set email alerts
|

Eccrine Hidrocystoma Arising at the Tarsal Plate during Childhood

Abstract: A 2-year-old boy with an upper-eyelid tumor in his right eye underwent complete resection. Pathological examination showed that the tumor was composed of a thin wall, lined by a single cuboidal epithelium, and contained a transparent liquid. The epithelium of the tumor wall did not display decapitation and the tumor was diagnosed as eccrine hidrocystoma. After resection, obvious improvement of the tumor-caused blepharoptosis was observed and the visual acuity of the patient recovered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…A thorough review of the reported cases showed a total of 10 cases of periocular eccrine hidrocystoma; only 5 were orbital in origin (Table 1). In addition to the present case, to the best of our knowledge, only two cases of congenital eccrine hidrocystoma have been reported so far 1 , 9 (Table 1). Malihi et al 1 operated on a 2-month-old boy with an orbital eccrine hidrocystoma presented with a bluish nodular non-tender subconjunctival swelling since birth.…”
Section: Discussionmentioning
confidence: 42%
See 1 more Smart Citation
“…A thorough review of the reported cases showed a total of 10 cases of periocular eccrine hidrocystoma; only 5 were orbital in origin (Table 1). In addition to the present case, to the best of our knowledge, only two cases of congenital eccrine hidrocystoma have been reported so far 1 , 9 (Table 1). Malihi et al 1 operated on a 2-month-old boy with an orbital eccrine hidrocystoma presented with a bluish nodular non-tender subconjunctival swelling since birth.…”
Section: Discussionmentioning
confidence: 42%
“…A giant lesion has been previously reported in the superior part of the orbit causing inferior dystopia and posterior eyelid lamellar inversion 11 Table 1The reported cases of eccrine hidrocystoma.No.Author & YearAgea/GenderPresenting symptomsCyst sizeOriginRadiologic features Eyelid 1Feijó et al 16 73/FBilateral multiple tumors on both eyelids.NAAcquiredNA2Hirata 2013 9 2/MUpper eyelid tumor with no pain or inflammation. The lesion was in direct contact with the tarsal plate.…”
Section: Discussionmentioning
confidence: 98%
“…[ 3 ] Eccrine hydrocystomas usually occur in the middle age, from the 4 th decade to the 8 th decade; however, it has been rarely reported in the younger age group also. [ 4 5 ] Solitary eccrine hydrocystomas occur equally in males and females, while multiple eccrine hydrocystomas have a female preponderance. [ 3 ] In our case, a middle-aged male patient presented with multiple eccrine hydrocystoma.…”
mentioning
confidence: 99%
“…Multiple eccrine hydrocystomas mainly affect the face and neck, largely confined to the cheeks and eyelids;[ 1 ] as seen in our case also. However, several uncommon locations have been reported, namely, eyelid,[ 2 ] tarsal plate,[ 5 ] upper lip,[ 6 ] external ear canal,[ 7 8 ] and the pericoccygeal region. [ 9 ]…”
mentioning
confidence: 99%